Archimedean atomic lattice effect algebras with complete lattice of sharp elements - Riecanova, Z. (Symmetry, Integrability and Geometry: Methods and Applications, 2010)
We study Archimedean atomic lattice effect algebras whose set of sharp elements
is a complete lattice. We show properties of centers, compatibility centers and central atoms of such lattice ef fect algebras. Moreover, we prove that if such effect algebra E is separable and modular then there exists a faithful state on E. Further, if an atomic lattice effect algebra is densely embeddable into a complete lattice effect algebra Eb and the compatibility center of E is not a Boolean algebra then there exists an (o)-continuous subadditive state on E.